Frequency of pelvic floor disorders and related socio-demographic and obstetric determinants in reproductive aged women in Tabriz city, 2021-2022 - Fatemeh Rashidi; Mojgan Mirghafourvand (Mashhad University of Medical Sciences, 2024)
Introduction: Pelvic floor disorders are one of the most common morbidities in women, which have negative consequences on women's daily life. Since the total prevalence of this disorder among Iranian's women has not been reported by appropriate tools, this study was conducted with aim to determine the prevalence of pelvic floor disorder and its risk factors. Methods: This cross-sectional study was conducted in 2021-2022 on 400 non-pregnant women of reproductive age referring to Tabriz health centers. Data related to pelvic floor disorders were collected through the Australian Pelvic Floor Questionnaire and the Sociodemographic and Obstetric Characteristics Questionnaire. Data were analyzed using SPSS software (version 26) and Chi-square test and multivariate logistic regression. P<0.05 was considered significant. Results: In this study, 264 participants (66.0%) had pelvic floor disorder.  Also, 191 participants (47.8%) had urinary incontinence, 235 (58.8%) had fecal incontinence, 52 (13.0%) had pelvic organ prolapse, and 271 (67.8%) had sexual dysfunction. The odds of pelvic floor disorder was lower in women with primary education (odds ratio (OR): 0.46; 95% confidence interval (95% CI): 0.24 to 0.86; P=0.016) and women who exercised (OR: 0.55; 95% CI: 0.35 to 0.86; P=0.009). History of vaginal delivery (OR: 2.37; 95% CI: 1.41 to 3.96; P=0.001) and having constipation (OR: 3.37; 95% CI: 1.62 to 7.00; P<0.001) significantly increased the odds of pelvic floor disorders. Conclusion: Pelvic floor disorders were common among participated women. The results of the study highlight specific risk factors in the management and prevention of pelvic floor disorders. Therefore, screening and preventive measures are suggested by health workers considering its risk factors.